The Volcanoes of Indonesia And Natural Disaster Reduction - Herman Th. Verstappen (Faculty of Geography, Universitas Gadjah Mada, 1994)
Indonesian volcanism is related to the subduction (genie zones of the Lido-Australian and the Pacific-Philippine plates at the contact with the Asian plate. Rows of volcanoes perpendicular to the plate movement point to steepening of the subduction zone. with time. Strafo volcanoes and also ignimbrite plateaus associated with socalled